Biosorption of cu(ll) onto sulfuric acid treated spent grated coconut (cocos nucifera) in fixed-bed column / Nurul Sahida Mohd Shukri - Mohd Shukri, Nurul Sahida (Faculty of Applied Sciences, 2017)
Spent grated coconut treated with sulphuric acid had been evaluated as a potential low cost biosorbent. It had been used for the removal of copper(II) from the aqueous solution using fixed-bed column mode. The parameters were fixed for this study using; 50 mg/L influent concentration, 10 mL/min flow rate, 1.5 cm bed-depth and pH 5. The adsorption capacity obtained from breakthrough curve was 35.785 mg/g. The breakthrough time, tb at 71.57 min, while t50% at 118.36 min and exhaustion time, texh at 211.23 min for 2050 mL. The R2 of Thomas model was 0.885 and qo was 66.50 mg/g while R2 of Yoon-Nelson model was 0.879 and qoYN was 66.75 mg/g.